2023
DOI: 10.1021/acs.jpclett.3c01527
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Reverse the Supramolecular Chirality of Insulin Fibrils

Abstract: Long-chain unsaturated and polyunsaturated fatty acids (LCUFAs and LCPUFAs, respectively) are the essential components of phospholipids and sphingolipids, major building blocks of plasma and organelle membranes. These molecules are also involved in cell signaling and energy metabolism. Hence, both LCUFAs and LCPUFAs are broadly used as food supplements. However, the role of these fatty acids (FAs) in the self-assembly of misfolded proteins remains unclear. In this study, we investigated the effect of LCUFAs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Specifically, all ω-3 LCPUFAs strongly accelerated protein aggregation, whereas ω-6 and other LCUFAs and LCPUFAs could or could not exert similar effects on the rate of protein aggregation. Using molecular docking simulations, Holman and co-workers recently showed that the ω-3 C18:3 LCPUFA has much lower binding energy to insulin compared to C22:6, C20:5, C16:1, C18:0, and C18:1 LCPUFAs and LCUFAs . Although no calculations were made for C18:4 (ω-3 LCPUFAs) and C18:2 (ω-6 LCPUFAs), these results indicate that observed differences in the rate of protein aggregation could be linked to the more favorable interaction of ω-3 LCPUFAs with insulin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, all ω-3 LCPUFAs strongly accelerated protein aggregation, whereas ω-6 and other LCUFAs and LCPUFAs could or could not exert similar effects on the rate of protein aggregation. Using molecular docking simulations, Holman and co-workers recently showed that the ω-3 C18:3 LCPUFA has much lower binding energy to insulin compared to C22:6, C20:5, C16:1, C18:0, and C18:1 LCPUFAs and LCUFAs . Although no calculations were made for C18:4 (ω-3 LCPUFAs) and C18:2 (ω-6 LCPUFAs), these results indicate that observed differences in the rate of protein aggregation could be linked to the more favorable interaction of ω-3 LCPUFAs with insulin.…”
Section: Resultsmentioning
confidence: 99%
“…Using molecular docking simulations, Holman and co-workers recently showed that the ω-3 C18:3 LCPUFA has much lower binding energy to insulin compared to C22:6, C20:5, C16:1, C18:0, and C18:1 LCPUFAs and LCUFAs. 29 Although no calculations were made for C18:4 (ω-3 LCPUFAs) and C18:2 (ω-6 LCPUFAs), these results indicate that observed differences in the rate of protein aggregation could be linked to the more favorable interaction of ω-3 LCPUFAs with insulin. Microscopic examination of protein aggregates formed in the presence of LCUFAs and LCPUFAs revealed the presence of fibril species that had similar dimensions to the protein aggregates formed in the UFA-free environment.…”
Section: Morphological Examination Of Insulin Aggregates Grown In The...mentioning
confidence: 90%
“…It was also found that hydrophobic interactions between insulin and FAs were strongly altered by the number of carbon atoms in FAs and the degree of their unsaturation. 50 The results summarized in this Account also suggest that the onset and progression of amyloid diseases could be linked to the pathological changes in plasma membranes. For instance, an increase in the concentration of PS in the external membrane, which takes place in the case of cell malfunctioning, can trigger the aggregation of amyloidogenic proteins.…”
Section: ■ Concluding Remarksmentioning
confidence: 90%
“…As a result, inulin:FAs complexes formed fibrils with opposite supramolecular chirality compared to those developed by insulin in a lipid-free environment. It was also found that hydrophobic interactions between insulin and FAs were strongly altered by the number of carbon atoms in FAs and the degree of their unsaturation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation